TIME OF FLIGHT SECONDARY ION MASS SPECTROMETRY (TOFSIMS) OF A NUMBER OF HOPANOIDS - Steele A.; Toporski J.K.W.; Avci R.; Guidry S.; McKay D.S. (My University, 2001)
Time of flight secondary ion mass spectrometry (ToFSIMS) has been applied to a number of bacterial hopanoids in an attempt to characterise these geologically important molecules in situ by a surface sensitive technique. Our results show that these molecules can be detected using this instrumentation to a high degree of mass accuracy. We believe that ToFSIMS can, therefore, be used to identify these molecules in environmental samples where sample size may be an issue and contraindicate the use of more traditional techniques such as GC-MS.